E-learning di era pandemi covid-19: Bagaimana aksiologi hasil belajar pendidikan jasmani? - Aulia Gusdernawati; Povian Yona Mahatmasari; Wawan S Suherman; Ahmad Nasrulloh; Kamilia Lituhayu; Aji Khotibul Umam (Journal Of Sport Education (JOPE), 2021)
The implementation of education in schools contains values including responsibility, discipline, independence, honesty, creativity and social. The Covid-19 pandemic that is currently happening has become a barrier to learning in schools so that it is diverted online. The aim that you want to know in this study is how the axiology in physical education learning through e-learning in the era of the Covid-19 pandemic? This research is a correlational study using a population of junior high schools in Yogyakarta. The research subjects were 120 people. The sampling technique was chosen randomly by random sampling technique. The data collection instrument used a questionnaire with a Likert scale type with a validity and reliability value of the questionnaire with a value of 0.887. The results of this study explain that there is no axiological value relationship in physical education learning through e-learning in the Covid-19 pandemic era with a significant value of 0.264. The axiological value obtained is included in the low category of physical education learning through e-learning in this pandemic era. In this online learning, it is hoped that students can still increase the value of axiology. This increase can be done by habituation in the environment of students, both family, school and socialCopyright © The Author (s) 2021Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.